Weight gain as a surrogate marker of longer survival in advanced non-small cell lung cancer patients - Topkan, Erkan (Annals of Translational Medicine, 2016)
Weight loss (WL), as a key step of the irreversible and fatal cancer-related anorexia cachexia syndrome is present to some degree in 80% of non-small cell lung cancer (NSCLC) patients upon diagnosis which has been clearly proved to negatively alter patients’ performance status, quality of life (QOL), response to treatment, and prognosis. However, WL is not a problem encountered only upon diagnosis but is also commonly reported during the course of aggressive chemotherapy, radiotherapy (RT) and particularly the concurrent chemoradiotherapy (C-CRT) which may further diminish QOL measures and clinical outcomes. In general, the NSCLC literature has concentrated on WL during the treatment course, but recent studies have demonstrated that it is possible to preserve or even experience weight gain (WG) during or just short after the discontinuation of various cancer treatments in approximately 40% to 45% NSCLC patients. Considering the fact that recent evidence suggest a prognostic and predictive role for WG in anticipation of longer survival times and better response rates in weight gainers, this current manuscript will specifically aim to realize the actual value of WG in locally advanced and metastatic NSCLC patients which may potentially be added to the conventional prognostic and predictive factors as a novel surrogate marker of outcomes in such patients.